Sosialisasi Hukum Tentang Dampak Pernikahan Usia Dini Terhadap Tingkat Perceraian Dimasa Pandemi Covid 19 di Lombok, NTB - opan, opansatriamandala; Zubaedi; Sakti, Lanang; Saputra, Sahdan; Hayati, Ridha Nurul; Aprianto, Dedi (Institut Agama Islam Hamzanwadi NW Pancor, 2022)
The number of early marriages in Indonesia has increased dramatically during the Covid-19 pandemic even though the law in Indonesia has regulated the minimum age limit for marriage is 19 years, as stipulated in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974. Someone who marries below the limit This age is classified as early marriage. Early marriage is a marriage that is carried out legally by a man or woman who has not had the preparation and maturity so that it is feared that they will experience a number of big risks. This big risk will even be an influence in terms of health during childbirth. This service aims to increase knowledge, understanding and awareness about the factors that lead to early marriage and the impact of early marriage on divorce rates during Covid 19. This service uses the Normative Law method. The approach used is a statutory approach, a conceptual approach and a historical approach. Based on the results of this service, it shows that the factors that cause early marriage are education, family economy, avoiding pregnancies outside of marriage, social media, school closures and the Covid 19 factor and the impact of early marriage on the divorce rate during the Covid 19 era is marriage. Early childhood has a number of negative impacts, especially for women, such as reproductive health and the economy. However, the number actually increased in Indonesia during the Covid-19 pandemic. The number of women marry early correlates with divorce.